2022
DOI: 10.1148/ryai.210026
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Multiple Diseases on Body CT Scans Using Weakly Supervised Deep Learning

Abstract: To design multidisease classifiers for body CT scans for three different organ systems using automatically extracted labels from radiology text reports. Materials and Methods:This retrospective study included a total of 12 092 patients (mean age, 57 years 6 18 [standard deviation]; 6172 women) for model development and testing. Rule-based algorithms were used to extract 19 225 disease labels from 13 667 body CT scans performed between 2012 and 2017. Using a three-dimensional DenseVNet, three organ systems were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…We demonstrated that the models trained on a large amount of data labeled by a language model outperformed those trained on smaller datasets labeled by experts, as shown in Figure 6. Additionally, compared with a previous study that used reports as training labels, 24 our pipeline showed at least a 7% improvement in the AUC for organ-specific abnormality detection. This improvement may be due to the accuracy of the information extraction schema.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We demonstrated that the models trained on a large amount of data labeled by a language model outperformed those trained on smaller datasets labeled by experts, as shown in Figure 6. Additionally, compared with a previous study that used reports as training labels, 24 our pipeline showed at least a 7% improvement in the AUC for organ-specific abnormality detection. This improvement may be due to the accuracy of the information extraction schema.…”
Section: Discussionmentioning
confidence: 70%
“…Only two studies to date have used reports as labels for CT images: one focused on the head region, with images collected from two institutions, 13 while the other targeted two abdominal regions (liver/gallbladder and kidney), using a total of 9,153 images from a single institution, which yielded an anomaly-detection performance of at least 7% lower than that of our pipeline. 24 Abnormality detection in abdominal CT images is challenging, because these scans provide high-resolution images of large areas including multiple organs. These images cannot be directly used in AI due to their size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been substantial prior work on multipleabnormality prediction in different modalities; chest CT [1], body CT [2], chest x-ray for COVID-19 [3] and 3D MRI for brain tumor classification [4]. However, constructing multiclass (i.e., pathology) classifiers for 3D medical data isn't a straightforward undertaking and remains challenging because of two main obstacles: acquiring sufficiently large datasets and learning effective representations with weak pathological footprints.…”
Section: Introductionmentioning
confidence: 99%